Athens Remains: A Greek Archaeology of the Present (Journal of Greek Media & Culture, 2019)
A special issue of the Journal of Greek Media and Culture (5.2), edited by Dimitris Plantzos. With a special focus on the city of Athens and its current predicament of austerity, recession and precarity, the issue brings together cultural historians, social anthropologists, urban archaeologists and contemporary artists in order to compose ‘a Greek archaeology of the present’. The new special issue includes articles by Penelope Papailias, Neni Panourgiá, Stelios Lekakis, Charis Kanellopoulou, Faidon Moudopoulos and Dimitris Giannakis; a visual essay by Penelope Petsini; and a viewpoint-piece by novelist Christos Chrissopoulos. This new collection of articles and essays attempts a re-charting of Athens as a city in the process of spatial and social restructuring; as a field of cultural expression, as well as a deeply traumatized, multi-cultural community in awe of its own urbanization. To this end, individual contributions explore the biopolitics of the ‘Greek crisis’; the gentrification of urban space; the commodification of cultural life; the restructuring of public memory; the renegotiation of collective histories within an urban setting.